Murder on Memory Lake - Griffo, J. D. (Griffo, J. D. Ferrara family mystery., 2018)
Alberta Scaglione<U+2019> s spinster aunt had some secrets<U+2014>like the fortune she squirreled away and a secret lake house in Tranquility, New Jersey. More surprising: she<U+2019>s left it all to Alberta. Alberta, a widow, is no spring chicken and she<U+2019>s gotten used to disappointment. So having a beautiful view, surrounded by hydrangeas, honeysuckle, and her cat, Lola, sounds blissful after years of yelling and bickering and cooking countless lasagnas. But Tranquility isn<U+2019>t as peaceful as it sounds. There<U+2019>s a body in the water<U+2014>and it belongs to Alberta<U+2019>s childhood nemesis. Alberta suspects foul play and when Alberta<U+2019>s estranged granddaughter, an aspiring crime reporter, shows up, it only makes sense for them to team up and investigate . . .